Determination of location of historical and cultural heritage objects using photogrammetric and geophysical methods - Borys Chetverikov; Ihor Trevoho; Lyubov Babiy; Mariia Malanchuk (Geodesy and Cartography)
Two central problems related to the study of historical fortification systems are apparent. First, there are high labour costs for the excavation of defensive structures. Therefore, studying each line of defence along its entire length by traditional archaeological methods is practically impossible. That’s probably why special studies of the fortification system are the exception rather than the rule, and information about defensive structures is given in single sections. The second problem is related to the fact that some lines of fortifications were destroyed in ancient times or were practically destroyed due to later economic activity. The specified circumstances determine the need to use photogrammetric and geophysical methods for the preliminary search of the infrastructure of defence structures. This work provides an example of deciding mass graves during the Second World War using the interpretative properties of German aerial photographs of 1944, archival cartographic data on the territory of the Lviv Citadel, where the Nazi concentration camp for prisoners of war Stalag-328 was located during the war. After predetermining the places of mass graves by photogrammetric methods, geophysical surveys were carried out with the help of ground-penetrating radar (GPR) for the exact localisation of the graves. 13 locations of mass burials and mass executions and burning of bodies of prisoners of war were discovered.